Dalla Festa Della Libertà Creativa All'economia Del Dono - Bazzichi, Oreste (Miscellanea francescana, 2017)
Having as a background the rich, profound and multi-annual scientific production of Orlando Todisco, this contribution, rather than analyzing and commenting on the texts dealing with socio-economic issues, simply limits itself to follow and intercept the relationship, correlation and conjugation between the "epistemology of the Franciscan School, equally in the sense of historical and doctrinal as well as the philosophical-theological; and in the socio-economic and political implications, highlighting a specific, current and stimulating common research path with many areas still to be discovered and dissected. Todisco's attention to philosophical themes of a practical and social dimension, above all, arises from the real and concrete questions of ethical, anthropological and social relevance that lead him from the feast of creative freedom to the logic of Franciscan thought to be applied in the socio-economic value of the bond and the conjugation according to which the true is true if it is in serving of the good and the good is good if it is free.